Evaluasi Perilaku Tarik Pelat Baja Ringan melalui Pendekatan Eksperimental dan Simulasi Finite Element Method (FEM) - Y Djoko setiyarto (Institut Teknologi Garut, 2026)
Accurate strain measurement is a crucial aspect of material tensile testing because it directly affects the determination of mechanical properties such as the modulus of elasticity and yield stress. In laboratory practice, strain measurement often relies solely on displacement records from the Universal Testing Machine (UTM), although such measurements are potentially affected by grip slip and deformation of the clamping system. This study evaluates the tensile behavior of lightweight steel plates through an experimental approach focusing on the comparison of strain measurement accuracy using three methods: the UTM, strain gauges, and displacement transducers (LVDT). Tensile test specimens were taken from lipped channel profiles with thicknesses of 1.5 mm and 2 mm, and then tested in accordance with ASTM A370 standards. The test results show that the strain recorded by the UTM was significantly greater than the strain measured using strain gauges and transducers, particularly during the plastic phase, due to the accumulation of slip at the grips. The strain differences could reach more than 20 times at certain stress levels, potentially leading to misinterpretation of the material’s tensile behavior. Strain gauges provided accurate strain measurements during the elastic phase, while transducers were capable of recording strain up to near-fracture conditions. The findings of this study confirm that the use of additional instruments is essential to obtain representative stress–strain curves and to improve the reliability of tensile test results for lightweight steel plates in structural engineering applications.